Kontribusi Wisata Spiritual Terhadap Perekonomian Bali : Studi Pada Wisata Spritual Tirta Empul di Kabupaten Gianyar - Hibatullah, Naufal; Fasandra, Fernando; Nova, Siska Mitria (Institut Seni Indonesia Padangpanjang, 2022)
In the last 10 years the development of tourist travel trends has been marked by the emergence of motivation and patterns of new travel, towards alternative or special interest tourism. Spiritual tourism is a new trend in the world of tourism which tends to increase.This paper uses the documentation method. The focus in this paper is to seek the contribution of spiritual tourism to the Balinese economy. located at Tirta Empul Temple, Gianyar Regency, Bali Province.The results of this paper show the direct economic benefits of spiritual tourism in Tirta Empul are the income received by business unit owners, inns and travel agents. The indirect economic benefits of spiritual tourism in Tirta Empul are workers and suppliers who work in tourism businesses and services in the area. The continued economic benefit of spiritual tourism in Tirta Empul is expenditure by workers who work in the area of the tourist attraction.